Serotype-Specific Protection Against Treponema hyodysenteriae Infection in Ligated Colonic Loops of Pigs Recovered from Swine Dysentery - Joens, L. A. (1983)
Resistance to Treponema hyodysenteriae (serotypes 1, 2, 3, and 4) infection was evaluated in ligated colonic loops in pigs recovered from swine dysentery. Lesions were present in most loops from recovered swine inoculated with heterologous serotypes; however, lesions were not present in loops of recovered swine inoculated with homologous serotypes.